Steady state analysis of power transmission using unified power flow controller - Mustafa, Mohd. Wazir (2002)
This paper presents the application of UPFC in steady-state analysis and demonstrates the capabilities of UPFC in controlling real and reactive power flow within any electrical network. The PWM based UPFC model is implemented in Single Machine Infinite Bus system and 22-bus IEEE test system. To demonstrate the performance of PWM based UPFC model in power system, both power system networks have been simulated using PSCAD/EMTDC. From the simulation results, it has been shown that the UPFC controller is capable of controlling independently real and reactive power flow through the transmission line. It has also been shown that UPFC can be used for voltage support.